Microbial degradation mechanisms of the neonicotinoids acetamiprid and flonicamid and the associated toxicity assessments - Sun, Shilei; Guo, Jingjing; Zhu, Zhi; Zhou, Jiangsheng (Frontiers in Microbiology, 2024)
Extensive use of the neonicotinoid insecticides acetamiprid (ACE) and flonicamid (FLO) in agriculture poses severe environmental and ecological risks. Microbial remediation is considered a feasible approach to address these issues. Many ACE-and FLO-degrading microorganisms have been isolated and characterized, but few reviews have concentrated on the underlying degradation mechanisms. In this review, we describe the microbial degradation pathways of ACE and FLO and assess the toxicity of ACE, FLO and their metabolites. Especially, we focus on the enzymes involved in degradation of ACE and FLO, including cytochrome P450s, nitrile hydratases, amidases, and nitrilases. Those studies reviewed here further our understanding of the enzymatic mechanisms of microbial degradation of ACE and FLO, and aid in the application of microbes to remediate environmental ACE and FLO contamination.